Ratio Analysis of the Degree of Decentralization, Regional Financial Independence, Regional Financial Dependence, Effectiveness in the City of Medan Local Own-Source Revenue - Khairi, Ilham; Nasution, Yenni Samri Juliati; Rahmani, Nur Ahmadi Bi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This research aims to analyze the degree of decentralization ratio, independence ratio, dependency ratio, and effectiveness ratio in local revenue Local Own-source Revenue reports in order to increase the financial independence of the Medan City Government during the 2021-2023 period. The type of analysis method used is quantitative analysis with a descriptive approach to Medan City PAD data during that period. The research results show that the degree of concentration for independence and effectiveness of Medan City's PAD has increased gradually from 2021 to 2023. However, the dependency ratio still shows quite high numbers, indicating that dependence on external sources of income is still a challenge. The implication of these findings is the need for further efforts to increase the financial independence of the Medan City Government by reducing dependence on external sources of income and increasing the efficiency of local revenue management.